Association of daily physical activity with hypertension, depressive symptoms, loneliness, and poor sleep quality in aged 60–79 older adults - Kaili Yan; Shengfang Gao; Qiuyu Sun; Kaijuan Wang (Scientific Reports, 2024)
Abstract This study aimed to assess its relationship between physical activity with health-related indicators in older population of the China. Cross-sectional data of 1,327 individuals aged 60–79 years were analyzed. Based on the Fifth National Physical Fitness Monitoring Program, depressive symptom and loneliness were measured using the Patient Health Questionnaire-9 and Emotional versus Social Loneliness Scales, respectively. Sleep quality was evaluated through self-designed questionnaire and hypertension was defined as blood pressure > 140/90 mmHg. International Physical Activity Questionnaire-Long Form was conducted to assess the physical activity (minutes and frequency) in different domains (domestic, transport, work, and leisure). Multivariable-adjusted binary logistic regression models estimated for the prevalence of health-related indicators, considering PA level, duration, frequency, and combinations of different domains of PA. In the study, favorable associations were observed between moderate to high level PA and reductions in 4 health-related indicators, especially for active frequency. Moreover, a combination of transport, domestic, and leisure PA was found to be a general protective factor for health-related indicators. In summary, this study highlights the positive impact of PA on older adults’ health and provides valuable insights into the role of different PA patterns, offering a theoretical basis for developing PA guidelines, policies, and health interventions.